Realizing a mid-infrared optically pumped molecular gas laser inside hollow-core photonic crystal fiber - Jones, Andrew Michael (Kansas State University, 2012)
This research has focused on the development, demonstration, and characterization of a new type of laser based on optically-pumped gases contained within hollow optical fibers. These novel lasers are appealing for a variety of applications including frequency metrology in the mid-infrared, free-space communications and imaging, and defense applications. Furthermore, because of the hollow core fibers used, this technology may provide the means to surpass the theoretical limits of output power available from high power solid-core fiber laser systems. Gas-filled hollow-core fiber lasers based on population inversion from acetylene ([superscript]12C[subscript]2H[subscript]2) and hydrogen cyanide (HCN) gas contained within the core of a kagome-structured hollow-core photonic crystal fiber have now been demonstrated. The gases are optically pumped via first order rotational-vibrational overtones near 1.5 μm using 1-ns duration pulses from a home-built optical parametric amplifier. Narrow-band laser emission peaks in the 3-μm region corresponding to the ΔJ = ±1 dipole allowed rotational transitions between the pumped vibrational overtone modes and the fundamental C-H stretching modes have been observed in both molecules. High gain resulting from tight confinement of the pump and laser light together with the active gas permits these lasers to operate in a single pass configuration, without the use of any external resonator structure. Studies of the generated mid-infrared pulse energy, threshold energy, and slope efficiency as functions of the launched pump pulse energy and gas pressure have been performed and show an optimum condition where the maximum laser pulse energy is achieved for a given fiber length. The laser pulse shape and the laser-to-pump pulse delay have been observed to change with varying pump pulse energy and gas pressure, resulting from the necessary population inversion being created in the gases at a specific fiber length dependent on the launched pulse energy. Work is on going to demonstrate the first continuous wave version of the laser which may be used to produce a single coherent output from many mutually incoherent pump sources.
Keywords: Molecular gas lasers; Mid-infrared lasers; Fiber lasers; Photonic Crystal Fiber; Optics (0752)